Review of Incadorcus Arnaud & Bomans with the description of three new species from the Yungas of Peru and Bolivia (Coleoptera: Lucanidae: Lucaninae) - Grossi, Paschoal Coelho (Zootaxa, 2011)
Three new species of the genus Incadorcus are described from Junín, Peru, and Coroico and Carrasco, Bolivia. The new species are compared with related species and illustrated. Dorsal habitus, head, pronotum, elytra and male genitalia of all species are figured and a distribution map is included. Incadorcus cuzcoensis Arnaud, Noguchi & Bomans is elevated to species status and Incadorcus kirchneri Schenk is synonymized with Incadorcus michellae Arnaud & Bomans. The species Metadorcus rufolineatus Nagel and Aegognathus nigrosuturalis Weinreich are transferred to the genus Onorelucanus.